KOSOVO* SPECIALIST CHAMBERS: ORIGINS, LEGAL NATURE, AND POLITICAL ROLE IN THE CONTEXT OF TRANSITIONAL JUSTICE - Ilić, Milica (Srpska politička misao, 2026)
This paper examines the legal nature and institutional framework of the Kosovo Specialist Chambers and the Office of the Specialist Prosecutor. The author offers a critical analysis of the establishment process, institutional structure, and political function of the Specialist Chambers, with particular emphasis on the role of the European Union in their creation and operational activities. The study also addresses the key jurisprudential challenges these institutions face. Special attention is devoted to the functioning to date of the Specialist Chambers and the Office of the Specialist Prosecutor – institutions established within the legal system of the self-proclaimed Republic of Kosovo, mandated to investigate and prosecute serious crimes committed in Kosovo and Metohija between 1998 and 2000. The methodological framework of the paper includes both normative and critical methods, with the aim of determining the legal nature and re-examining the functioning of these institutions through the analysis of international legal instruments. In addition to the positivist legal approach, the paper also presents a critical theoretical framework.